How skilful communication won the real story: A Timor-Leste theatre of intimidation, retrospective and ‘Anti-News’ - Max Stahl (Pacific Journalism Review, 2015)
This is an extract from a keynote address by film maker and journalist Max Stahl, director of the Centro Audiovisual Max Stahl Timor-Leste (CAMSTL), at the 20th anniversary conference of Pacific Journalism Review in November 2014. Stahl screened the first part of an ‘experimental’ film, The Reconciliation—a kind of ‘anti-news’—and spoke about his methodology and stylistic approach in achieving something mainstream news, almost by definition, cannot. It tells the deeper story, or the many possible stories according to those actually involved inside the story, of a week in Timor Leste in 1999 prior to its independence from Indonesia. It is challenging. There are no resumés available. It is outside the privileged world of news.